Spiderwort in bloom - Lindquist, Mark, photographer (Colorado State University. Libraries, 2000)
TROC, Tradescantia occidentalis, spiderwort in bloom with purple flowers, on SGS.
Keywords: flowers; SGS; spiderwort; plants